Damping and energy dissipation in soft tissue vibrations during running. Issue 2 (21st January 2015) - Khassetarash, Arash; Hassannejad, Reza; Enders, Hendrik; Ettefagh, Mir Mohammad
Abstract It has been well accepted that the vibrations of soft tissue cannot be simulated by a single sinusoidal function. In fact, these vibrations are a combination of several vibration modes. In this study, these modes are extracted applying a recently developed method namely, partly ensemble empirical mode decomposition (PEEMD). Then, a methodology for estimating the damping properties and energy dissipation caused by damping for each mode is used. Applying this methodology on simulated signals demonstrates high accuracy. This methodology is applied to the acceleration signals of the gastrocnemius muscle during sprinting and the differences between the damping properties of different vibration modes were identified. The results were 1) the damping property of high-frequency mode was higher than that for low-frequency modes. 2) All identified modes were in under damped condition, therefore, the vibrations had an oscillatory nature. 3) The damping ratios of lower modes are about 100% increased compared to higher modes. 4) The energy dissipation occurred in lower modes were much more than that for higher mode; According to the power spectrum of the ground reaction force (GRF), which is the input force into the body, the recent finding supports the muscle tuning paradigm. It is suggested that the damping properties and energy dissipation can be used to distinguish between different running conditions (surface, fatigue, etc.)